Eichmann's men - Safrian, Hans 1952- (Cambridge University Press, 2010)
"More than sixty years after the advent of the National Socialist genocides, the question still remains: how could a state-sponsored terror that took the lives of millions of men, women, and children, persecuted as Jews or Gypsies, happen? Now available in English, Hans Safrian's path-breaking work on Adolf Eichmann and his Nazi helpers chronicles the escalation of Nazi anti-Semitic policies beginning in 1933 and during World War II to the "final solution." This book examines a central group of National Socialist perpetrators who expelled German, Austrian, and Czech Jews from their homelands and deported massive numbers of them to the ghettos, concentration camps, and killing centers of occupied Eastern Europe. Safrian reconstructs the "careers" of Eichmann and his men in connection with the implementation of racial policies, particularly the gradual marginalization of their victims and the escalation from stigmatization, divestment, and segregation to deportation, forced labor, and, finally, mass murder"--Provided by publisher